2003
DOI: 10.1021/jm0205696
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Structure−Activity Relationship of Oxalylarylaminobenzoic Acids as Inhibitors of Protein Tyrosine Phosphatase 1B

Abstract: Protein Tyrosine phosphatase 1B (PTP1B) has been implicated as a key negative regulator of both insulin and leptin signaling pathways. Using an NMR-based screening approach with 15N- and 13C-labeled PTP1B, we have identified 2,3-dimethylphenyloxalylaminobenzoic acid (1) as a general, reversible, and competitive PTPase inhibitor. Structure-based approach guided by X-ray crystallography facilitated the development of 1 into a novel series of potent and selective PTP1B inhibitors occupying both the catalytic site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 23 publications
0
40
0
1
Order By: Relevance
“…PTP-1B has long been implicated in the regulation of insulin receptor tyrosine phosphorylation and tyrosine kinase activity [50], and has been validated as a bona fide pharmacological target for increasing insulin sensitivity [51][52][53][54][55]. In animals, small molecules that inhibit PTP-1B increase insulin sensitivity and lower plasma glucose [56][57][58]. Alternatively, chromium might act directly on the insulin receptor, and increase its tyrosine kinase activity [59], as has been observed with other small molecules [60,61].…”
Section: Discussionmentioning
confidence: 90%
“…PTP-1B has long been implicated in the regulation of insulin receptor tyrosine phosphorylation and tyrosine kinase activity [50], and has been validated as a bona fide pharmacological target for increasing insulin sensitivity [51][52][53][54][55]. In animals, small molecules that inhibit PTP-1B increase insulin sensitivity and lower plasma glucose [56][57][58]. Alternatively, chromium might act directly on the insulin receptor, and increase its tyrosine kinase activity [59], as has been observed with other small molecules [60,61].…”
Section: Discussionmentioning
confidence: 90%
“…As the basic structures of these inhibitors are charged, reasonable bioavailability was reported in rats. 143 From the SAR studies of the above reported series, various structural modifications have been attempted for higher and selective PTP 1B inhibitory activity. Various flexible linkers such as aminopentanoic acid (81) and phenylethylaminopentanoic acid (82) (Table XV) along with chiral amino sulfide such as (83) and (84) (Table XVI) showed increasing inhibitory potency as well as moderate selectivity.…”
Section: G 2-(oxalylamino)-benzoic Acidmentioning
confidence: 99%
“…2, CMS) and related acids Liljebris et al, 2002] and oxalylaminobenzoic (Fig. 2, OBA) and related acids Liu et al, 2003a] have been used as pTyr mimetics but still yield molecules that carry a strong negative charge at physiological pH. While attempts have been made to replace the carboxylic acids with bioisosteres, such as tetrazole with reduced anionic charge and improved permeability , they have not led to molecules with sufficient overall properties to be considered as drug candidates.…”
Section: Toward the Discovery And Design Of Small Molecule Ptp1b Inhimentioning
confidence: 99%